Evolutionary trajectory of undifferentiated connective tissue disease and impact of 2019 EULAR/ACR systemic lupus erythematosus classification criteria: insights from a longitudinal study - Ciancarella, Claudia; Ceccarelli, Fulvia; Picciariello, Licia; Natalucci, Francesco; Celia, Alessandra Ida; Garufi, Cristina; Mancuso, Silvia; Tripodi, Giuseppe; Truglia, Simona; Gattamelata, Angelica; Spinelli, Francesca Romana; Alessandri, Cristiano; et al. (Clinical and experimental medicine, 2025)
Undifferentiated connective tissue disease (UCTD) is a condition characterized by serological evidence of autoimmunity and occurrence of clinical symptoms suggestive for systemic autoimmune diseases, yet not fulfilling specific classification/diagnostic criteria. In the present longitudinal, observational, retrospective study, we aimed at analysing the evolution of UCTD course, focussing on the impact of 2019 EULAR/ACR classification criteria for systemic lupus erythematosus (SLE). Since 2008 we consecutively collected data about UCTD patients. All subjects were evaluated every six months, to record the development of clinical and laboratory features suggestive for specific autoimmune diseases. Finally, we retrospectively applied the 2019 EULAR/ACR SLE classification criteria at the first and last visit in our outpatient clinic. All the patients included in the study had been evaluated at our Lupus Clinic before the release of 2019 EULAR/ACR criteria. We included 201 UCTD patients [F/M 191/10, median age at first visit 46 years (IQR 21), median disease duration at first visit 3 years (IQR 9)]. At the first visit, 27 patients (13.4%) already met 2019 EULAR/ACR SLE classification criteria. Logistic regression analysis demonstrated the association between SLE classification and thrombocytopenia, anti-dsDNA/anti-Sm positivity, low C4 levels, joint involvement. During a mean observation period of 45.9 ± 35.6 months, 18.9% of patients were lost to follow-up, while 141 patients were followed. At last visit, additional 11 patients (7.8%) could be classified as having SLE. A relevant proportion of UCTD patients could be reclassified as having SLE according to the most recent classification criteria. Thrombocytopenia, anti-DNA/anti-Sm positivity and low C4 levels represent the most associated factors.